Cost-effectiveness analysis of left atrial appendage occlusion in patients with atrial fibrillation and contraindication to oral anticoagulation. (17th December 2021) - Labori, Frida; Persson, Josefine; Bonander, Carl; Jood, Katarina; Svensson, Mikael
Abstract: Aims: This study aims to estimate the cost-effectiveness of percutaneous left atrial appendage occlusion (LAAO) compared to standard stroke prevention care for patients with atrial fibrillation (AF) and contraindication to oral anticoagulation (OAC) in a Swedish healthcare and public sector perspective. Methods and results: We used a combined decision tree and cohort Markov model to estimate costs and quality-adjusted life-years (QALYs) over a lifetime horizon with LAAO compared to standard of care where the treatment effect is based on a recent meta-analysis. According to our analysis, LAAO gives more QALYs than standard of care (7.11 vs. 6.12). Furthermore, LAAO treatment is related to the first-year cost of 14 984 Euro (EUR) and higher average healthcare costs over the lifetime by about 4010 EUR, which gives an incremental cost-effectiveness ratio of LAAO vs. standard of care at 4047 EUR per gained QALY. From a public sector perspective, LAAO reduces average costs due to substantial reductions in long-term care and, thus, implies that LAAO is dominant from a public sector perspective (lower average costs and better health outcomes). Conclusion: From both Swedish healthcare and public sector perspectives, LAAO can be considered cost-effective compared to standard of care for individuals with AF and contraindication to OAC. However, these results must be confirmed in health economic evaluations alongside the ongoing randomized clinical trials. Key Question: Is left atrial appendage occlusion (LAAO) cost-effective for patients with atrial fibrillation (AF) and contraindication to oral anticoagulation (OAC) compared to the standard of care from a Swedish healthcare and public sector perspective? Key Finding: LAAO is associated with lower cost than the standard of care from a public sector perspective and an incremental cost of 4010 Euro from a healthcare perspective. Furthermore, LAAO is related to better health outcomes than the standard of care. Take Home Message: Treatment with LAAO among individuals with AF and contraindication to OAC can be considered as cost-effective compared to the standard of care from a Swedish healthcare and public sector perspective. Structured Graphical Abstract: